RAFFLESIA LAWANGENSIS (RAFFLESIACEAE), A NEW SPECIES FROM BUKIT LAWANG, GUNUNG LEUSER NATIONAL PARK, NORTH SUMATRA, INDONESIA - K. MAT -SALLEH; RIDHA MAHYUNI; AGUS SUSATYA; J.F. VELDKAMP (REINWARDTIA, 2010)
MAT-SALLEH, K., MAHYUNI, R., SUSATYA, A. & VELDKAMP, J. F. 2010. Rafflesia lawangensis (Rafflesiaceae), a new species from Bukit Lawang, Gunung Leuser National Park, North Sumatra, Indonesia. Reinwardtia 13(2): 159-165. - Rafflesia lawangensis (Rafflesiaceae), a new species from Bukit Lawang, Gunung Leuser National Park, North Sumatra is described. The species was previously recorded as either R. arnoldi or R. atjehensis, but it is distinguished by the absence of windows, the large undulating exterior annulus, the short pubescence on the upper surface of perigone lobes, and the very wide of diaphragm opening. A key to species of Sumatran Raffesia is provided.